Artificial intelligence applied to analyzes during the pandemic: COVID-19 beds occupancy in the state of Rio Grande do Norte, Brazil - Barreto, Tiago de Oliveira; Veras, Nícolas Vinícius Rodrigues; Cardoso, Pablo Holanda; Fernandes, Felipe Ricardo dos Santos; Medeiros, Luiz Paulo de Souza; Bezerra, Maria Valéria; Andrade, Filomena Marques Queiroz de; Pinheiro, Chander de Oliveira; Sánchez-Gendriz, Ignacio; Silva, Gleyson José Pinheiro Caldeira; Rodrigues, Leandro Farias; Morais, Antonio Higor Freire de; et al. (Frontiers in Artificial Intelligence, 2023)
The COVID-19 pandemic is already considered one of the biggest global health crises. In Rio Grande do Norte, a Brazilian state, the RegulaRN platform was the health information system used to regulate beds for patients with COVID-19. This article explored machine learning and deep learning techniques with RegulaRN data in order to identify the best models and parameters to predict the outcome of a hospitalized patient. A total of 25,366 bed regulations for COVID-19 patients were analyzed. The data analyzed comes from the RegulaRN Platform database from April 2020 to August 2022. From these data, the nine most pertinent characteristics were selected from the twenty available, and blank or inconclusive data were excluded.